Mapping The Readiness Of Students In Learning English Phase F Of The Independent Curriculum - Kustini, Titin (Papanda Publisher, 2023)
The Independent Curriculum gives teachers the freedom to choose material but focuses on strengthening the ability to use English in six language skills, namely listening, speaking, reading, viewing, writing, and presenting in an integrated manner, in various types of texts. The minimum learning outcomes for these six English skills refer to the Common European Framework of Reference for Languages: Learning, Teaching, Assessment (CEFR) and equivalent to level B1. The material for giving sympathy and appreciation is one of the materials given in class 11 semester 3. Even though the context of giving sympathy and appreciation is a common thing that happens in everyday contexts, for students to express it in English is quite a high difficulty. This case study occurred in learning English in class 11 Software Engineering 2. 30 participants involved in this study. Only 3 students were able to make sentences expressing sympathy after being given instructions by the teacher, the rest experienced quite high difficulties and needed intensive guidance to be able to complete the task. The main obstacles are lack of vocabulary, lack of grammatical knowledge and low motivation in learning English.